Production of silver nanoparticles via green method using banana raja peel extract as a reducing agent - Chafidz, Achmad; Afandi, Amira Rahmani; Rosa, Bunga Mela; Suhartono, Jono; Hidayat, Pratikno; Junaedi, Harri (Communications in Science and Technology, 2020)
In this study, biosynthesis of silver nanoparticles using the extract of a local banana peel (variant name: Raja) as bio-reductor was carried out. This study aimed to determine the effect of two different ratios of Banana Peel Extract (BPE)/distilled water on the synthesis of silver nanoparticles. The two of BPE/water ratios were 1% (v/v) and 5%(v/v), named as Sample A and Sample B, respectively. Whereas, the concentrations of AgNO3 solution as the precursor were varied as follows: 0.125; 0.1; 0.075; and 0.05 M. The synthesized colloidal silver nanoparticles were characterized using a UV-Vis spectrometer, while the BPE solution was analyzed using Fourier Transform Infra-Red (FT-IR) to study its functional groups. While, the solid silver nanoparticles was characterized using a Scanning Electron Microscopy (SEM) with an Energy-dispersive X-ray spectroscopy (EDX) analysis. The UV-Vis spectrometer results qualitatively showed that sample A produced better silver nanoparticles than that of sample B. All samples showed absorbance peaks at wavelength of 450 nm. It was found that the highest absorbance value (i.e. 1.59) occurred at sample A with a concentration of AgNO3 solution 0.1 M. Additionally, FT-IR analysis result showed the presence of a hydroxyl group specifically for alcohols as phenols, which indicated the possibility of polyphenol compounds. The SEM micrograph showed that some of the silver nanoparticles were in the shape of tetrahedron or triangular like particle and spherical The SEM image analysis results using ImageJ software showed that most of the silver nanoparticles produced had the size of 100-300 nm. Furthermore, the EDX analysis result showed a peak count at 3 keV, which confirmed the formation of silver nanoparticles.